Synergistic and antagonistic effect of gamma rays and ethyl methane sulphonate in mungbean (Vigna radiata) - SINGH, AWNINDRA K; SINGH, G P; SINGH, A P (The Indian Journal of Agricultural Sciences, 2011)
The experiments were conducted during 2003-05 to study the synergistic and antagonistic effect of gamma rays and ethyl methane sulphonate induced mutations in M1 and M2 generations in 2 genotypes of mungbean (Vigna radiata L. Wilczek). Effectiveness and efficiency of both mutagens in relation to induction of mutation was dose dependent and shows varietal specificity to the mutagens. Mutation frequency was proportional to doses of gamma rays and ethyl methane sulphonate, individually and in combination. Higher doses of both mutagens were found to be most effective in terms of reduction in values of character recorded. Combination treatments enhanced the pollen and ovule sterility as compared to the 2 mutagens individually. Difference in the response of both the cultivars due to mutagenic treatment indicates variation in the genetic architecture of the two cultivars.